METHODS OF DEVELOPING CRITICAL THINKING IN STUDENTS - Abdullajanova N. T. (Bright Mind Publishing, 2025)
Critical thinking has become one of the most essential skills in modern education. It enables students to analyze information, evaluate arguments, solve problems, and make informed decisions in a rapidly changing world. This paper explores various approaches and strategies for developing critical thinking skills in students. The discussion highlights theoretical perspectives, effective methods, practical classroom strategies, challenges faced by educators, and recommendations for improvement. By integrating both academic and practical insights, the article provides a comprehensive overview of how critical thinking can be cultivated in general educational contexts. The extended analysis also reflects on the role of culture, technology, and global perspectives in shaping critical thinking pedagogy
Keywords: Pedagogy, essential skills, critical thinking, effective methods